PENGEMBANGAN BAHAN AJAR MUTASI GENETIK PADA MATAKULIAH GENETIKA - Reza Ardiansyah; Aloysius Duran Corebima; Fatchur Rohman (Graduate School of Universitas Negeri Malang, 2017)
Teaching materials is one of the important components in learning that can help the smooth learning of students. The purpose of this research is to produce teaching material of genetic mutation in genetics course in State University of Malang. Development of teaching materials using Four-D development model. Data analysis is descriptive qualitative and quantitative descriptive. The result of development of teaching materials in the form of Module Genetic of mutation. The instructional materials in the form of modules have been revised based on the assessment of expert validators and small group trials. Based on the percentage of validity obtained from material expert validators, media experts and small group trials, the developed Module Genetic of mutation has met the valid criteria and can be used with the acquisition of percentages of 86.00%, 88.38%, and 88.38%. Product revisions are made based on comments and suggestions provided by validators and small group trials. Module Genetic of mutation comes with instructions for use, discussion, tasks, summary, test questions, reflections, answer keys, ratings, and glossary.Bahan ajar merupakan salah satu komponen penting dalam pembelajaran yang dapat membantu kelancaran belajar mahasiswa. Tujuan penelitian ini adalah untuk menghasilkan bahan ajar mutasi genetik pada matakuliah Genetika di Universitas Negeri Malang. Pengembangan bahan ajar menggunakan model pengembangan Four-D. Analisis data berupa data deskriptif kualitatif dan deskriptif kuantitatif. Hasil pengembangan bahan ajar berupa Modul Genetika Mutasi. Bahan ajar berupa modul telah direvisi berdasarkan hasil penilaian validator ahli dan uji coba kelompok kecil. Berdasarkan persentase kevalidan yang diperoleh dari validator ahli materi, ahli media dan uji coba kelompok kecil. Modul Genetika Mutasi yang dikembangkan telah memenuhi kriteria valid dan dapat digunakan dengan perolehan persentase masing-masing 86,00%, 88,38%, dan 88,38%. Revisi produk dilakukan berdasarkan komentar dan saran yang diberikan oleh validator dan uji coba kelompok kecil. Modul Genetika Mutasi ini dilengkapi dengan petunjuk penggunaan, diskusi, tugas, rangkuman, soal tes, refleksi, kunci jawaban, penilaian, dan glosarium.